TAX EDUCATION AND SOCIALIZATION FOR MSMEs AS AN EFFORT TO INCREASE TAX COMPLIANCE IN THE DIGITAL ERA - Loso Judijanto (Jurnal Pengabdian Masyarakat, 2025)
Tax is the main source of state revenue that is very important for national development, but the level of tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in Tangerang City is still relatively low. This Community Service Program (PkM) aims to improve tax literacy and compliance of MSME actors through digital-based tax education and socialization. The method used is Participatory Action Research (PAR) involving more than 100 MSME actors as participants. This activity was carried out through workshops, simulations of the use of digital tax applications, and interactive discussions. The results of the activity showed a significant increase in participants' understanding of tax obligations, with post-test scores increasing from 30% to 85% in terms of knowledge of types of taxes, as well as an increase in understanding of NPWP registration procedures and the use of digital tax applications. The positive impact of this program not only increases tax awareness among MSME actors, but also encourages them to utilize digital tax services independently. The conclusion of this activity emphasizes the importance of ongoing education and collaboration between the government and MSME actors to improve tax compliance. Recommendations for further development include organizing periodic education programs and establishing tax literacy communities at the local level.